Risk factors of chronic obstructive pulmonary disease among adults in Chinese mainland: A systematic review and meta-analysis. (October 2017) - Yang, Ying; Mao, Jing; Ye, Zhiying; Li, Jie; Zhao, Huimin; Liu, Yueting
Abstract: Background: Identifying risk factors is a key point for preventive strategies to reduce the incidence of COPD. The aim of this systematic review and meta-analysis was to determine the most important risk factors for COPD among adults in Chinese Mainland, so as to provide some precautions and interventions on this disease and preventing further recurrences. Methods: A comprehensive literature review relating to risk factors for COPD through PubMed, EMBASE, Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang database and VIP database was conducted before March 31, 2017. Odds ratio (OR) with 95% confidence interval (CI) was calculated after data combination to assess the associations between risk factors and COPD. Heterogeneity between the studies was assessed by I 2 and Cochran's Q test. Egger's test was used to assess publication bias. Results: A total of 13893 participants (6383 cases and 7510 controls) from 19 case-controls studies were included. 12 risk factors with significant differences found between COPD and control groups were listed as follows: male sex (OR = 1.467; 95%CI: 1.097–1.962), smoking (OR = 2.092; 95%CI: 1.707–2.565), low educational level (OR = 1.609; 95%CI: 1.206–2.147), low BMI (OR = 3.831; 95%CI: 2.223–6.603), family history of respiratory disease (OR = 2.068; 95%CI: 1.466–2.918), allergy history (OR = 2.381; 95%CI: 1.385–4.093), respiratory infection during childhood (OR = 2.695; 95%CI: 1.504–4.828), recurrent respiratory infection (OR = 15.015; 95%CI: 4.538–49.684), occupational dust exposure (OR = 1.791; 95%CI: 1.151–2.788), biomass burning (OR = 2.218; 95%CI: 1.308–3.762), poor housing ventilation (OR = 3.993; 95%CI: 1.244–12.820), and living around polluted area (OR = 1.631; 95%CI: 1.202–2.214). Conclusion: Twelve risk factors are associated with the occurrence of COPD in Chinese Mainland, which can be used to distinguish high-risk population. Health education and promotion campaigns should be designed in order to minimize or prevent the occurrence of COPD in Chinese Mainland. Highlights: Identifying risk factors is a key point for preventive strategies to reduce the incidence of COPD. Twelve risk factors are considered to be associated with the occurrence of COPD in Chinese Mainland. Risk factors of COPD can be used to distinguish high-risk population.